Where We’re At, What We Must Know, and Where We Can Go: A Systematic Review of Research about Writing and Artificial Intelligence - Eaton, Christopher; Belmonte, Isabella; Enaya, Talla; Flood, Sarah; Khalil, Zainab; Makwanda, Anthony; Shah, Mian Muhammad Ahmed; Toma, Alexia; Wang, Tiffany; Yu, Connor (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2025)
This paper reviews AI discussions to develop a thematic map of scholarship on AI, writing, and writing pedagogies. The project, developed between a university instructor and nine undergraduate students, had two central aims. The first was to synthesize the early research conversations on AI in writing contexts. The second was to identify gaps that will point to important next steps as the scholarly record on AI and writing develops. The paper presents five prominent themes: AI literacy, evaluating AI outputs, rhetoric in Human-AI interactions, AI and bias, and academic integrity. Conversations on AI literacy and academic integrity represent conceptual level discussions around AI and writing. The conversations around evaluation, rhetoric, and bias align more with AI writing practices and how these practices affect teaching and learning. Together, they provide a useful snapshot of scholarship and inform future work in a rapidly developing research conversation.